Business Ethics and Women Entrepreneurs, Sri Lanka - Jayawardane, V.P.T. (3rd International Conference for Accounting Researchers and Educators - 2017, 2017)
Women owned businesses in Sri Lanka, has increased significantly, creating a new generation of women entrepreneurs. This paper aims to outline the research connecting business ethics displayed by Sri Lankan women entrepreneurs when they are running successful businesses. Women entrepreneurs as decision makers come across ethical issues when managing their businesses. It has been identified that entrepreneurs come across ethical issues when they carry out their management responsibilities. Therefore, ethics and ethical perspectives in management are crucial for the success of women entrepreneurs. The focus of this paper is to encourage women entrepreneurs to maintain ethical practices that are essential for their business survival. This research was undertaken using data which was obtained using both primary and secondary sources. A structured questionnaire was used to obtain the primary data whilst secondary data was extracted from literature. Qualitative methodology was used for analysis and the total number of questionnaires distributed was 30 in a chosen sample of established women entrepreneurs of Sri Lanka. The study identified that there was a significant relationship between the ethical practices of the women entrepreneurs and the performance of their business. These findings contribute to a better understanding of how women entrepreneurs think and integrate business ethics into their decision-making. In conclusion, suggestions are made with essential business ethics which should be adopted by the women entrepreneurs in Sri Lanka as well as recommendations for future research.
Keywords: Women Entrepreneurs; Business Ethics; Successful Business; Sri Lanka